A comparative study on the effect of carbon fillers on electrical and thermal conductivity of a cyanate ester resin. (July 2017) - Wang, Xiao; Zhao, Yuntao; Jin, Jie; Song, Mo
Abstract: Carbon fillers including multi-walled carbon nanotubes (MWCNTs), carbon black (CB) and graphite were introduced in a cyanate ester (CE) resin, respectively. The effects of the fillers on the electrical and thermal conductivity of the resin were measured and analyzed based on the microscopic observations. MWCNTs, CB and graphite exhibited percolation threshold at 0.1 wt%, 0.5 wt% and 10 wt%, respectively. The maximal electrical conductivity of the composites was 1.08 S/cm, 9.94 × 10 −3 S/cm and 1.70 × 10 −5 S/cm. MWCNTs showed the best enhancement on the electrical conductivity. The thermal behavior of the composites was analyzed by calorimetry method. Incorporation of MWCNTs, CB and graphite increased the thermal conductivity of CE resin by 90%, 15% and 92%, respectively. Theoretical models were introduced to correlate the thermal conductivity of the CE/MWCNTs composite. The interfacial thermal resistance between CE resin and MWCNTs was 8 × 10 −8 m 2 K/W and the straightness ratio was 0.2. The MWCNTs were seriously entangled and agglomerated. Simulation results revealed that thermal conductivity of the CE/MWCNTs composites can be substantially elevated by increasing the straightness ratio and/or filler content of MWCNTs.